PERSISTENT INFECTION IN FREQUENT AND PROLONGED ILL CHILDREN, POSSIBILITIES OF ETIOPATHOGENETIC THERAPY - A. S. Levina; I. V. Babachenko (LLC "Diagnostics and Vaccines", 2015)
We present the results of the etiologic diagnosis and therapy of 243 frequent and prolonged ill children aged from 1 to 17 years. Microbiological, serological and molecular biological methods for the determination of bacterial agents, respiratory chlamydia and mycoplasma, Epstein-Barr virus, human herpes virus type 6 and cytomegalovirus were used. The dominant role of the active persistence of herpesviruses was shown (87%); bacterial pathogens were identified rarely, mainly in association with herpesvirus. 96 patients received a medication of recombinant interferon D-2 (VIFERON) and then endogenic interferon inductor, 57 patients - recombinant interferon D-2 (VIFERON) in conjunction with antibiotic therapy and then bacterial lysates. Treatment of children depending on the diagnosed infections allowed to achieve stable normalization of state in 78% of cases.